Prevalence and distribution of ampc beta-lactamase producing escherichia coli and klebsiella pneumoniae isolates obtained from urine samples at a tertiary care hospital in the caribbean - Thoms Rodriguez, Camille-Ann; Dawson, Felecia; Cameron, Jenene; Seah, Christine; Reid, Marvin; Melano, Roberto G.; Gossell-Williams, Maxine (Frontiers in Cellular and Infection Microbiology, 2022)
The aim of this study was to investigate the prevalence and distribution of plasmid-mediated AmpC (pAmpC) beta-lactamases (BLs) in uropathogens at the University Hospital of the West Indies Jamaica (UHWI). De-duplicated consecutive urine samples, collected from January to March 2020 at the UHWI, were analyzed. Screening and phenotypic confirmatory tests were conducted using resistance to cefoxitin and the Disc Approximation Test (DAT) respectively, for isolates without chromosomal AmpC genes. Multiplex PCR was performed on cefoxitin resistant (CR) isolates for the detection of blaCIT, blaMOX, blaFOX, blaACC, and blaDHA genes. Whole genome sequencing (WGS) was used to further detect pAmpC BL genes in PCR negative isolates with indeterminate phenotypic results. 64 isolates were obtained from 61 patients (55% female), ages18 months to 88 years old. At least 35% had complicated urinary tract infections. Only 7 out of 64 isolates had antibiograms suggestive of possible pAmpC BL production and were CR. DATs confirmed AmpC BL in two of these (1 Klebsiella pneumoniae; 1 Escherichia coli), one tested negative (E. coli) and four had inconclusive results (K. pneumoniae). PCR detected blaDHA and blaCIT in two CR isolates. WGS further detected blaCMY-42 in one isolate. The prevalence of screened CR isolates with pAmpC BL is 57.14 % (4 of 7), representing 6.25% of the study population. pAmpC BL producers had 100% susceptibility to meropenem and nitrofurantoin. pAmpC BL prevalence in the studied isolates is low. Cefoxitin screening is helpful however phenotypic screening using the DAT can yield indeterminate results best clarified by molecular testing.